2015
DOI: 10.1007/s10098-015-0920-2
|View full text |Cite
|
Sign up to set email alerts
|

Social acceptance of solar energy in Malaysia: users’ perspective

Abstract: The increase in energy demand has caused considerable attention to be directed toward sustainable energy resources. The importance of electricity generation through solar energy has been intensively highlighted globally, but Malaysia has yet to exert efforts to develop this energy resource. This study explores the social acceptance and level of human interest in solar energy. In addition, this work identifies the difficulties in the consumption of solar energy and the expectations for solar energy development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Table I summarises the estimated renewable potential in Malaysia. Since December 2011, the financial support mechanism of feed-in tariff has also been in place (Ahmad and Tahar, 2014b;Muhammad-Sukki et al, 2014). Though various studies have discovered that the general public in Malaysia is in favour of renewable technologies (Ahmad, et al 2015;Ahmad and Tahar, 2014c;Alam et al, 2014;Lim and Lam, 2014), there is a lack of understanding on the public attitudes and motivation to use renewable technologies, particularly solar PV technology (Solangi et al, 2015;Muhammad-Sukki et al, 2011). There are numerous studies available from developed counties evaluating the prospects of solar PV technology from the public's perspective (Musall and Kuik, 2011;Park and Oh, 2014;Schelly, 2014), but for developing countries, such as Malaysia, these studies are limited in number and are more focused on technical and policy considerations (Chua and Oh, 2012;Lau et al, 2009;Maulud and Saidi, 2012;Mekhilef et al, 2012;Murni et al, 2013;Nor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Table I summarises the estimated renewable potential in Malaysia. Since December 2011, the financial support mechanism of feed-in tariff has also been in place (Ahmad and Tahar, 2014b;Muhammad-Sukki et al, 2014). Though various studies have discovered that the general public in Malaysia is in favour of renewable technologies (Ahmad, et al 2015;Ahmad and Tahar, 2014c;Alam et al, 2014;Lim and Lam, 2014), there is a lack of understanding on the public attitudes and motivation to use renewable technologies, particularly solar PV technology (Solangi et al, 2015;Muhammad-Sukki et al, 2011). There are numerous studies available from developed counties evaluating the prospects of solar PV technology from the public's perspective (Musall and Kuik, 2011;Park and Oh, 2014;Schelly, 2014), but for developing countries, such as Malaysia, these studies are limited in number and are more focused on technical and policy considerations (Chua and Oh, 2012;Lau et al, 2009;Maulud and Saidi, 2012;Mekhilef et al, 2012;Murni et al, 2013;Nor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, two separate studies in the northern part of Pakistan and southern Punjab revealed that 81% and 82% of the respondents, respectively, were interested in RSPSs [65,66]. A study in Malaysia contended that 80% of the participants in the survey were highly interested in RSPSs [67].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [10] analyzed the feasibility of RE implementation by considering Korean customers' willingness to pay. Further, Solangi et al [11] studied the social acceptance of solar energy in Malaysia from the users' perspective. Particularly, Xu [12] researched the willingness to invest in a building that uses integrated photovoltaics and is grid-connected.…”
Section: The Related Literaturementioning
confidence: 99%
“…According to Equation (11) in Section 3, only one of the parameters θ, s − or s + can be chosen at this step. For example, after selecting the parameter, we need select θ, s − or s + in the drop-down list, and then click "Adjust"; then the adjusted I and O are received.…”
Section: The Adjustment Of Ineffective Decision-making Unitmentioning
confidence: 99%